Phytochemical analysis of aerial parts from Sida pyramidata Cav. Yerba de aura - Torres-Rodríguez, Eugenio; Núñez-Romero, Yisel Alina; Mojena-Guerra, Yurien; Fung-Boix, Yilan; Fonseca-Turruella, Yuneikis (Revista Cubana de Química, 2021)
Sida pyramidata Cav., well-known in Cuba as Yerba de aura, is traditionally used as a decoction of leaf sprouts to treat digestive disorders and diseases of the uterus. So far there are no reports of phytochemical studies on the plant that scientifically justify the attributed pharmacological properties. The objective of this work was to identify the secondary metabolites of biological and therapeutic interest present in the Sida pyramidata Cav. species. Phytochemical screening, performed on plant leaf extracts and applied thin layer chromatography, allowed to verify the presence of several families of secondary metabolites with pharmacological interest such as: saponins, essential oils, alkaloids, phenols and coumarins; being these with more abundance in the ethanol extract. The abundance of saponins, essential oils and alkaloids in Sida pyramidata Cav. It could be responsible for the pharmacological activity attributed to the plant.